Politics of race, gender, and visual representation in feminist media education. Issue 5 (2nd September 2020) - Dahya, Negin; King, W. E.
ABSTRACT: This paper discusses technologies of power and technologies of self in relation to race and gender in youth digital media production. We query how girls of color use feminist filmmaking to tell the stories they want to tell, and ask where the political discourse shaping their media production is located throughout the process. Our analysis is based on research conducted from 2015 to 2017 exploring traditional and mobile digital video production practices in non-profit media education programs. We offer a view to the cultural politics of digital video production in educational settings and focus on two final productions – an exposé about girls' empowerment and a horror genre inspired slasher film – each reproducing and subverting common themes of racial and gender-based oppression in and through digital media.